COVID-19 and suicides in India: A pilot study of reports in the media and scientific literature - Panigrahi, Mahima (Asian J Psychiatr, 2021)
BACKGROUND: Our objective was to analyze reports of COVID-19 related suicides (CRS) to identify associated factors with a broader goal to inform management and prevention strategies. METHODS: We searched scientific literature, government websites and online newspaper reports in English and nine regional languages to identify relevant CRS reports. RESULTS: A total of 151 CRS reports were retrieved. CRS was more frequently reported among males (80.8%), those whose COVID status was unknown (48.0%), and those in quarantine/isolation (49.0%). CONCLUSION: The above findings may assist identification of at-risk individuals for COVID-19 related suicidal behavior.